PENGARUH KREATIVITAS TERHADAP HASIL BELAJAR MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN SISWA SEKOLAH MENENGAH KEJURUAN NEGERI 6 YOGYAKARTA: PENGARUH KREATIVITAS TERHADAP HASIL BELAJAR MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN SISWA SEKOLAH MENENGAH KEJURUAN NEGERI 6 YOGYAKARTA - Umar, Nur Alawiah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2025)
The purpose of this research is to determine the effectiveness of creativity on the learningoutcomes of creative and entrepreneurial products of class XI students of fashion design atState Vocational High School 6 Yogyakarta. This type of research is a quantitative study usingdocumentation and questionnaire data collection methods. The results showed that (1) therewas effectiveness and significance of creativity on the results of the subject value of creativeproducts and entrepreneurship in class XI of fashion with rcount 0.569> rtabel 0.279.(2) thecreativity of class XI students of fashion design is in the high category with a relative frequencyof 44.23%, and (3) The learning outcomes of creative products and entrepreneurship are inthe high category with a relative frequency of 48.1%.